Catalytic asymmetric sulfenylation to structurally diverse dithioketals. Issue 90 (24th September 2015) - Liao, Kui; Zhou, Feng; Yu, Jin-Sheng; Gao, Wei-Ming; Zhou, Jian
Abstract : We report the first example of highly enantioselective synthesis of structurally diverse chiral dithioketals via asymmetric sulfenylation of various types of S-based nucleophiles, catalyzed by a cheap cinchona alkaloid derivative, dihydroquinine. Abstract : We report the first example of the highly enantioselective synthesis of structurally diverse chiral dithioketals via asymmetric sulfenylation of various types of S-based nucleophiles, catalyzed by a cheap cinchona alkaloid derivative, dihydroquinine.